Formation Process and Properties of Ohmic Contacts Containing Molybdenum to AlGaN/GaN Heterostructures - Wojciech Macherzynski; Jacek Gryglewicz; Andrzej Stafiniak; Joanna Prazmowska; Regina Paszkiewicz (Advances in Electrical and Electronic Engineering, 2016)
Properties of wide bandgap semiconductors as chemical inertness to harsh conditions and possibility of working at high temperature ensure possible applications in the field as military, aerospace, automotive, engine monitoring, flame detection and solar UV detection. Requirements for ohmic contacts in semiconductor devices are determined by the proposed application. These contacts to AlGaN/GaN heterostructure for application as high temperature, high frequency and high power devices have to exhibit good surface morphology and low contact resistance. The latter is a crucial factor in limiting the development of high performance AlGaN/GaN devices. Lowering of the resistance is assured by rapid thermal annealing process. The paper present studies of Ti/Al/Mo/Au ohmic contacst annealed at temperature range from 825°C to 885°C in N2 atmosphere. The electrical parameters of examined samples as a function of the annealing process condition have been studied. Initially the annealing temperature increase caused lowering of the contacts resistance. The lowest value was noticed for the temperature of annealing equal to 885°C. Further increase of annealing temperature led to deterioration of contact resistance of investigated ohmic contacts.